Yield and Farmer Preferences of Biofortified Orange-Fleshed Sweetpotato Varieties under Drought-Prone Conditions in Malawi - Longwe, K.; Munda, E.; Mello Kapezi, R.; Kuweruza, F.; Chipungu, Felistus P.; Mamboya, P.; Chadzala, T.; Jogo, W. (2024)
The study evaluated the agronomic performance, root yield, and farmer preferences for biofortified orange-fleshed sweetpotato (OFSP) varieties across four districts in Malawi Balaka, Mangochi, Salima, and Zomba under drought-prone conditions. Five OFSP varieties; Chipika, Kaphulira, Kadyaubwerere, Royal Choice, and Mathuthu were assessed at two harvesting stages, 3 and 5 months after planting (MAP), to determine vine weight and storage root yield. Root yield performance varied significantly among OFSP varieties and districts at both 3 and 5 MAP, with Chipika consistently outperforming other varieties. At 5 MAP, Chipika recorded the highest total root yield across districts, reaching 17.7 t/ha in Balaka and 17 t/ha in Zomba, followed by Royal Choice with 16.2 t/ha in Zomba. Despite yields being below the national average (19 t/ha), the early harvestability of some varieties at 3 MAP and their adaptability to low rainfall conditions highlight their potential to mitigate climate change impacts in drought-prone areas. Participatory variety selection was conducted to capture farmer preferences at vegetative and harvesting stages. A total of 414 farmers participated in the variety selection, including 199 women and 215 men. Farmers prioritized traits such as early maturity, marketable root yield, root size, and drought resilience. Chipika emerged as the most preferred variety due to its high yield potential and early maturity, which align with household food security and nutritional needs. Women emphasized traits like early maturity and leafy vegetable potential, while men focused on drought tolerance and structural resilience, reflecting gender-specific priorities. The study concludes that OFSP varieties have significant potential as climate-resilient crops to enhance food and nutrition security in drought-prone areas of Malawi. The findings underscore the importance of integrating agronomic performance with farmer preferences to guide the scaling and dissemination of OFSP varieties. Further study required to assess the seasonal effects on OFSP varieties yield.